In vitro and in vivo toxicity of urban and rural particulate matter from California. (February 2015) - Mirowsky, Jaime E.; Jin, Lan; Thurston, George; Lighthall, David; Tyner, Tim; Horton, Lori; Galdanes, Karen; Chillrud, Steven; Ross, James; Pinkerton, Kent E.; Chen, Lung Chi; Lippmann, Morton; et al.
Abstract: Particulate matter (PM) varies in chemical composition and mass concentration based on location, source, and particle size. This study sought to evaluate the in vitro and in vivo toxicity of coarse (PM10-2.5 ) and fine (PM2.5 ) PM samples collected at 5 diverse sites within California. Coarse and fine PM samples were collected simultaneously at 2 rural and 3 urban sites within California during the summer. A human pulmonary microvascular endothelial cell line (HPMEC-ST1.6R) was exposed to PM suspensions (50 μg/mL) and analyzed for reactive oxygen species (ROS) after 5 h of treatment. In addition, FVB/N mice were exposed by oropharyngeal aspiration to 50 μg PM, and lavage fluid was collected 24 h post-exposure and analyzed for total protein and %PMNs. Correlations between trace metal concentrations, endotoxin, and biological endpoints were calculated, and the effect of particle size range, locale (urban vs. rural), and location was determined. Absolute principal factor analysis was used to identify pollution sources of PM from elemental tracers of those sources. Ambient PM elicited an ROS and pro-inflammatory-related response in the cell and mouse models, respectively. These responses were dependent on particle size, locale, and location. Trace elements associated with soil and traffic markers were most strongly linked to the adverse effects in vitro and in vivo . Particle size, location, source, and composition of PM collected at 5 locations in California affected the ROS response in human pulmonary endothelial cells and the inflammatory response in mice. Highlights: The toxicity of particulate matter was assessed at 5 California locations. Urban locations and coarse particles elicited the greatest biological effects. Soil and traffic markers were associated with the measured biological effects. Particle sources might be more influential than size when determining toxicity.